Sweden's pensioners: how they have fared in the roller coaster ride through the past decade and a half of deep recession and economic exuberance - Björn Gustafsson; Mats Johansson; Edward Palmer (Institute for the Study of Labor (IZA), 2007)
This study analyses the development of the economic well-being of the elderly in Sweden since 1990 - a period characterized by increased influence from the financial market and extreme economic events using data from the Household Income Survey. The elderly were not isolated as pensions were cut, full indexation abandoned and taxes increased during Sweden's deep recession in the 1990s. Instead, relatively, pensioners fared better than the working age population. On the other hand, poverty increased in absolute terms. In contrast in the following years of rapid economic growth, the growth in the income of the pensioners fell behind that of workers and relative poverty increased. The analysis shows that the limited resources of many of the elderly put them close to a socially interesting poverty line. Income inequality among the elderly has increased with an increase in the importance of capital income for the better off among the elderly, with a clear tendency towards delineation between the better and worse off, which we conclude has implications for public expenditures for the elderly. Overall, poverty among the elderly in Sweden remains low in an international perspective and our analysis leads us to conclude that the Swedish welfare state has maintained its resilience.
Keywords: D31; 330; Sweden; pensions; income; poverty; income inequality; Rentner; Lebensstandard; Alte Menschen; Einkommensverteilung; Armut; Sozialstaat; Schweden